Persepsi staf wanita terhadap kemudahan dan perkembangan kerjaya di Universiti Teknologi Malaysia - Abdul Rahman, Hamidah; Bakri, Norhani; Mohd. Balwi, Mohd. Koharudin; Abd. Rahman, Siti Aisyah; Zaini, Fadhilah; Bahari, Siti Fatimah (Faculty of Management and Human Resource Development, 2004)

(untitled)
The primary purpose of this study is to identify UTM Skudai female staffs perception towards physical and spiritual facilities as well as career development. The total of 380 from 1495 academic and non-academic female staffs at all units and faculty were selected as respondents by using simple random sampling. The data were analysed based on percentage and frequency by using Statistical Package For Social Sciences (SPSS). Finding showed that event though basic physical facilities are provided such as toilet, prayer room and sport facility, it is still consider not suitable and in uncamfortable state. Finding also revealed that sick bay and female restroom were not provided by UTM at all units or faculty. In terms of spiritual facilities, study showed that most of the respondents agreed that religious activities and Darul Syifa’ practitioner should be conducted by ustazah. On top of that, the need for female counsellor is very critical. This is because, all this while there was no female counsellor provided in handling female staffs’ problem. For career development, female staffs were treated unfairly because they acquire less opportunity for promotion as well as not trusted to be at the management position in their department or faculty.